2001
DOI: 10.1101/gad.918201
|View full text |Cite
|
Sign up to set email alerts
|

Substrate recognition by the Cdc20 and Cdh1 components of the anaphase-promoting complex

Abstract: The specificity of ubiquitin-mediated protein degradation with regards to the selection of substrates to be polyubiquitinated has only been determined rather recently. Substrate targeting by the N-end rule and HECT (homology to E6AP carboxyl terminus) domain ubiquitin ligases occurs through substrate-specific binding domains. In contrast, the SCF complex recruits substrates through a substrate adaptor protein, the F-box subunit. Despite evidence showing that Cdc20 and Cdh1 bind and activate the anaphase-promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
215
3
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(230 citation statements)
references
References 58 publications
8
215
3
4
Order By: Relevance
“…The association between VHL and the elongin BC complex is mediated by the SOCS-box motif of VHL (Kamura et al, 1998). The substrate recognition factors of APC are the WD40 repeat-containing proteins Cdc20 and Cdh1 (Burton et al, 2001;Hilioti et al, 2001;Pfleger et al, 2001). We have observed direct binding between Cdc20 or Cdh1 and the APC2/11 ubiquitin ligase core (our unpublished data).…”
Section: Substrate Recognition By Apc and Its Regulation During Cell mentioning
confidence: 85%
See 2 more Smart Citations
“…The association between VHL and the elongin BC complex is mediated by the SOCS-box motif of VHL (Kamura et al, 1998). The substrate recognition factors of APC are the WD40 repeat-containing proteins Cdc20 and Cdh1 (Burton et al, 2001;Hilioti et al, 2001;Pfleger et al, 2001). We have observed direct binding between Cdc20 or Cdh1 and the APC2/11 ubiquitin ligase core (our unpublished data).…”
Section: Substrate Recognition By Apc and Its Regulation During Cell mentioning
confidence: 85%
“…Binding of either Cdc20 or Cdh1 to APC increases the activity of APC drastically (Fang et al, 1998;Kramer et al, 1998). Although the exact mechanism by which Cdc20 and Cdh1 contribute to the ubiquitination reactions is unknown, several recent observations suggest that they might be directly involved in substrate recruitment (Schwab et al, 1997;Sigrist and Lehner, 1997;Visintin et al, 1997;Burton et al, 2001;Hilioti et al, 2001;Pfleger et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further specific and direct interactions of Cdc20 with Pds1 and of Cdh1/Hct1 with Clb2, Clb3 and Cdc5 were also demonstrated in budding yeast (Burton and Solomon, 2001;Schwab et al, 2001). Finally, Pfleger et al (2001a) showed that in the absence of APC, Cdc20 and Cdh1/Hct1 can directly and specifically bind a large number of APC substrates including Xkid, securin, geminin, cyclin A and cyclin B.…”
Section: Substrate Recognitionmentioning
confidence: 89%
“…Comparison between structures of the SCF and APC suggests a putative role of these activators in substrate recognition. In this regard, recent results have shown that different APC substrates can directly and specifically bind to Cdc20 and Cdh1/Hct1 (Fang et al, 1998b;Burton and Solomon, 2001;Sorensen et al, 2001;Pfleger et al, 2001a).…”
Section: Apc Activators: Cdc20 Cdh1 and Ama1mentioning
confidence: 99%